The contradictory unity of faith and reason in Christian theoretical thought - Astapov, Sergey N. (HTS teologiese studies, 2019)
This article aims to demonstrate the unity of faith and reason as irrational and rational elements of the theoretical religious discourse on instances of Christian theoretical thought. This unity was represented as a dialectical contradiction, the violation of which led to the destruction of religious discourse. The contradictory unity of faith and reason was researched in European medieval philosophy and Russian religious philosophy in the first half of the 20th century and in the theoretical systems that were considered ways of explaining the relationship between faith and reason in Christian thought. This article reveals two historical types of the dynamic unity of faith and reason as well as violations of this unity: when medieval authors attempted to find the most effective relationship between faith and reason for Christian theology; and when Russian philosophers attempted to transmit theological knowledge by means of philosophy in the secular age. The results of the dynamic unity violations in both traditions are investigated as the conceptions that had been denied by these traditions. The main conclusion of the article is that Christian theoretical thought maintained the contradictions between faith and reason as a search for its development.